2002
DOI: 10.1128/jvi.76.23.12149-12161.2002
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Bioluminescence Imaging of Herpes Simplex Virus Type 1 Infection and Therapy in Living Mice

Abstract: Mouse models of herpes simplex virus type 1 (HSV-1) infection provide significant insights into viral and host genes that regulate disease pathogenesis, but conventional methods to determine the full extent of viral spread and replication typically require the sacrifice of infected animals. To develop a noninvasive method for detecting HSV-1 in living mice, we used a strain KOS HSV-1 recombinant that expresses firefly (Photinus pyralis) and Renilla (Renilla reniformis) luciferase reporter proteins and monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 32 publications
3
141
0
2
Order By: Relevance
“…[46] Bioluminescence Imaging of Animals Human T cell trafficking in NOD/SCID-β2m null recipients was assessed non-invasively by bioluminescence with an IVIS 100 CCD camera (Xenogen, Alameda, CA, USA) as described. [47,48] Briefly, mice were injected i.p. with D-luciferin (150 μg/g in PBS) and imaged 10 min later with the IVIS (1-60 sec exposure, binning 8, f-stop 1, FOV 15 cm).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…[46] Bioluminescence Imaging of Animals Human T cell trafficking in NOD/SCID-β2m null recipients was assessed non-invasively by bioluminescence with an IVIS 100 CCD camera (Xenogen, Alameda, CA, USA) as described. [47,48] Briefly, mice were injected i.p. with D-luciferin (150 μg/g in PBS) and imaged 10 min later with the IVIS (1-60 sec exposure, binning 8, f-stop 1, FOV 15 cm).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…After in vivo images were taken, cells were lysed to determine total protein and corrected for total protein in each well. Data analysis was performed as described (16).…”
Section: Methodsmentioning
confidence: 99%
“…Although previous data suggested that Rluc could be used for reporter imaging in mice in vivo (15), limited utility and poor bioavailability of coelenterazine was reported in a mouse model of viral infection with an Rluc reporter strain of herpes simplex virus 1 (16). Interestingly, anabolic enzymes enabling de novo synthesis of coelenterazine are lacking in many bioluminescent organisms, and a dietary requirement for coelenterazine within the food chain has been demonstrated (17), implying mechanisms for absorption and retention of the compound.…”
mentioning
confidence: 99%
“…Since the light is scattered due to the refractive index at cell membranes and organelles, the spatial resolution of bioluminescence imaging is approximately 2-3 mm. 38 This is low in comparison to imaging modalities that use more penetrating radiation such as positron emission tomography, single positron emission computed tomography and computed tomography. 37 Furthermore, the imaging data are in a two-dimensional format; so, the light detected is a consequence of all light emitted in a given plane, and further method development is needed to produce three-dimensional imaging/cross-sectional imaging.…”
Section: Discussionmentioning
confidence: 98%
“…Although viral DNA could be detected in the heart, bioluminescence imaging of mice did not reveal luciferase expression in this region, and this may be accounted for by an insufficient number of cells being infected and expressing luciferase. It is generally accepted that 10 6 cells need to express luciferase before detection can be achieved, 38 in addition to which the heart is shielded by the ribcage which may reduce detectable light compared to the lower abdomen. Heparan sulphate has been identified as the cell surface receptor for the HVS homologue human herpesvirus-8, 39 and it is likely that HVS shares the same receptor.…”
Section: Discussionmentioning
confidence: 99%